Photoperiod-dependent correlation between light-induced SCN c-fos expression and resetting of circadian phase - Trávnícková, Z; Sumová, A; Peters, R; Schwartz, W J; Illnerová, H (The American journal of physiology, 1996)
In rodents, brief light pulses that shift the phase of the circadian locomotor rhythm also increase c-fos gene expression in the suprachiasmatic nucleus (SCN), site of an endogenous clock that regulates such rhythmicity. Because the magnitude of photic phase shifts varies when light pulses are applied at different time points over the course of the subjective night, we examined the degree of SCN c-fos gene expression after single 30-min light pulses were delivered at time points that spanned the early and late subjective night in rats maintained in either short (8:16-h light-dark cycle) or long (16:8-h light-dark cycle) photoperiods. The light-induced level of c-fos mRNA and the number of cells expressing immunoreactive c-Fos protein were measured in the SCN by in situ hybridization and immunohistochemistry, respectively, and compared with the magnitude of the corresponding phase shifts of the circadian rhythm of pineal N-acetyltransferase (NAT) activity. We found a robust correlation between c-fos photoinduction and NAT phase shifts, but this relationship was dependent on photoperiod. The degree of c-fos gene expression was strongly correlated with the magnitude of NAT phase advances and delays under the short photoperiod and with phase advances under the long photoperiod, but not with phase delays under the long photoperiod. The data suggest that c-fos gene expression in the SCN may be involved in the photic resetting of the pineal NAT rhythm. Under the long photoperiod, however, the magnitude of phase delays may be limited by the functional state of the circadian pacemaking system.
Keywords: hybridizace in situ; RNA, Messenger; fotoperioda; Male; Rats, Wistar; Photoperiod; In Situ Hybridization; imunohistochemie; mužské pohlaví; Suprachiasmatic Nucleus; potkani Wistar; cirkadiánní rytmus; světlo; Circadian Rhythm; krysa rodu Rattus; Time Factors; Animals; Immunohistochemistry; nucleus suprachiasmaticus; zvířata; Rats; časové faktory; protoonkogenní proteiny c-fos; Light; messenger RNA; Proto-Oncogene Proteins c-fos